Supramolecular structure and technofunctional properties of starch modified by high hydrostatic pressure (HHP): A review. (1st September 2022) - Dominguez-Ayala, Jaime E.; Soler, Adrian; Mendez-Montealvo, Guadalupe; Velazquez, Gonzalo
Abstract: This review focuses on describing and discussing recent findings regarding the effects of high hydrostatic pressure (HHP) on the supramolecular structure and technofunctional properties of starch, as well as on analyzing the hypothesis to explain these changes. The non-thermal modification of starch through HHP involves complex supramolecular structural changes that depend on the botanical source, amylose content, and treatment intensity. Overall, the granular morphology, lamellar and crystalline structures, and double helices undergo different degrees of modification/disorganization during HHP, but these changes are distinguished from thermal modification by an improvement at the same gelatinization degree. The HHP-induced supramolecular modifications determine the properties of starch, including water solubility, swelling power, pasting, water and oil holding capacity, thermal properties, and in vitro digestibility. Graphical abstract: Unlabelled Image